Computer Graphical Interfaces, Reflection and the Teaching and Learning of Music Composition - a Holistic Study. - JENNINGS, KEVIN GERARD (Trinity College Dublin.School of Computer Science and Statistics.COMPUTER SCIENCE, 2006)
This thesis is a holistic study in the area of teaching and learning of music composition for children in the age range eight to eleven years. It investigates the role of graphical computer technology within the framework of a reflection-in-action model for teaching, learning and research. Its primary aims are firstly: to examine if reflection-in-action provides a valid model for description of the behaviour and interactions of teachers, learners and researchers in a technology-enabled environment, and secondly; to investigate how technology enables/facilitates this model in the case of each. This is done through both examination of both childrens and teachers behaviours, processes and strategies as they work together with graphical music software, and also by analysis of childrens compositional products. Two pieces of software were developed, one designed solely by the author (DrumSteps), the other in collaboration with research students at MIT (Hyperscore). Each piece of software was extensively deployed in a wide range of settings with children in the 9-12 year age range. Qualitative data were collected by intensive examination of selected teaching and learning situations, using digital video capture to providing a complete record of all learner and teacher actions. Analysis of the resulting data indicated that Schon?s reflection-in-action model is applicable to technology-mediated teaching and learning of music composition. The graphical interfaces were observed to provide a valuable empowering mechanism for both teachers and learners, facilitating music learning interactions that would not be possible otherwise. Learner interactions progressed through clear stages and learners exhibited definable, context-related behaviours. Both pieces of software were made available to the public via the TCD, MIT and BBC websites and users were invited to submit examples of their work, yielding over ten thousand pieces, of which two hundred and fifty were selected for analysis. A marked difference was noted in the nature and quality of childrens pieces produced in mentored workshops and those collected via the web, indicating that the presence of a teacher is a necessary component for deeper musical learning and reflection. Effective technology-mediated teaching strategies were identified. Use of graphical software in tandem with digital video capture was further demonstrated to be an effective vehicle for researcher reflection, yielding unique insight into music teaching and learning.
APPROVED
Keywords: Computer Science